Динамическая модель для эвольвентного прямозубого зацепления - Бережной, Виталий Александрович; Матюшенко, Николай Васильевич; Федченко, Анна Валерьевна (НТУ "ХПИ", 2012)
A dynamic model is examined for cylindrical spur gears. From the system of differential equalizations of the dynamic system equalizations of determination of gain-frequency characteristics of gearing are got.
Dynamic model for cylindrical spur gears
Keywords: цилиндрическое зацепление; зубчатая передача; колебания